Efeitos de variáveis físicas e químicas na decomposição de recursos vegetais terrestres alagados em reservatórios - Fonseca, Andre Luiz dos Santos (2011)
Reservoirs provide many benefits (e.g. recreation, water supply, electricity production) to human populations. However, the damming of a water body changes the characteristics from lotic to lentic environment. These changes affect the physical, chemical and biological ecosystem, such as the current velocity, the ecosystem depth, the light penetration, the amount of decomposed biomass, the oxygen consumption. In this context, this study aimed to evaluate the influence of physical and chemical variables (detritus quality, aerobic and anaerobic condition, current velocity and hydrostatic pressure) on the decomposition of terrestrial plant resources (leaves, branches and litter) that remain in the flooded area during the formation of the reservoirs. The results showed that: i) labile compounds of leaf litter consumed more dissolved oxygen in the initial stage of decomposition, according to their greater fragility and DOC amount. In addition, the accumulated dissolved oxygen consumption showed two phases during decomposition of debris, indicating that the composition of DOC was heterogeneous, ii) the mass loss of debris was greater in aerobic than in anaerobic condition; iii) the water velocity increased the mass loss of leaf and branches detritus due their abrasive effect. The mass loss was higher in leaf debris, according to their major fragility and higher surface area and volume ratio, iv) the hydrostatic pressure (equivalent to 30 and 100 m depth) did not influence the decomposition of leaves and branches detritus; v) the detritus quality was a factor that determined the action of environmental variables studied (dissolved oxygen availability and current velocity) on the detritus decomposition process.